2013
DOI: 10.1111/ijn.12095
|View full text |Cite
|
Sign up to set email alerts
|

Motivations to nurse: An exploration of what motivates students in Pacific Island countries to enter nursing

Abstract: The aim of this study was to explore the motivations of student nurses enrolled in nursing courses across a variety of Pacific Island countries. The image of nursing, the desire to help others, family and friends in the profession, personal experience, security, travel opportunities and flexibility have all been identified as motivators for people to enter nursing. To date, what motivates students in Pacific Island countries to enrol in a nursing course has not been investigated. An exploratory qualitative app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The positive attitudes of the nurses towards nursing care may have several possible explanations. Perceived core values that are attached to the profession of nursing act as resources that help nurses achieve moral competence and adherence to their intrinsic work-related values, and this may enable nurses to enjoy their work and be more satisfied, 8,[29][30][31] despite challenges, such as limited resources, high workload, and low salaries. The study revealed a significant difference in attitude between nurses who had held their current positions for less than 4 years and those who had held their posts for longer periods.…”
Section: Nurses' Attitudesmentioning
confidence: 99%
“…The positive attitudes of the nurses towards nursing care may have several possible explanations. Perceived core values that are attached to the profession of nursing act as resources that help nurses achieve moral competence and adherence to their intrinsic work-related values, and this may enable nurses to enjoy their work and be more satisfied, 8,[29][30][31] despite challenges, such as limited resources, high workload, and low salaries. The study revealed a significant difference in attitude between nurses who had held their current positions for less than 4 years and those who had held their posts for longer periods.…”
Section: Nurses' Attitudesmentioning
confidence: 99%
“…Although novice nurses start working with a passion for the profession because of their motivation to help other people (Glearean, Hupli, Talman, & Haavisto, ; Usher et al, ), experiences in the first year may have a significant impact on their future career plans and professional commitment (Brown, Hochstetler, Rode, Abraham, & Gillum, ). Starting in clinical practice, nurses are confronted with many stressful and dissatisfying situations (Laschinger, Leiter, Day, & Gilin, ; Liang, Lin, & Wu, ) due to a heavy workload, patients with complex care demands (comorbidity) and conflicting job demands (cognitively or physically overburdened).…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for becoming a nurse are a subject of interest for researchers, who apply both quantitative and qualitative approaches when studying them. The desire to help or care for others is reported by researchers in many countries [ 10 – 15 ]. Other reasons for becoming a nurse are the availability of training close to home, pure chance, recommendation from family and friends, and not being able to get into any other study program [ 12 ].…”
Section: Introductionmentioning
confidence: 99%